ANALYSIS OF THE DRIVER’S POSITION IN THE TRAFFIC SYSTEM AND THE INFLUENCE ON THE LEVEL OF TRAFFIC SAFETY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Improvement of the mechanism of driver training and assessment of its impact on ensuring traffic safety and implementation of modern methods of driver training.